The effects of exercise programs on cognition, activities of daily living, and neuropsychiatric symptoms in community-dwelling people with dementia-a systematic review - Steichele, Kathrin; Keefer, Anne; Dietzel, Nikolas; Grässel, Elmar; Prokosch, Hans-Ulrich; Kolominsky-Rabas, Peter (Alzheimer's Research and Therapy, 2022)
Background: The prevalence of dementia is expected to increase dramatically. Due to a lack of pharmacological treatment options for people with dementia, non-pharmacological treatments such as exercise programs have been recommended to improve cognition, activities of daily living, and neuropsychiatric symptoms. However, inconsistent results have been reported across different trials, mainly because of the high heterogeneity of exercise modalities. Thus, this systematic review aims to answer the questions whether exercise programs improve cognition, activities of daily living as well as neuropsychiatric symptoms in community-dwelling people with dementia.
CRIS-Team WoS Importer:2022-08-05